Answer:
![2√(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2azg64i6u27lwc5uo20taee6di6t41dkfw.png)
=====================================
Step-by-step explanation:
Let's say we replace every copy of
with x
Doing so means we have the expression 5x-3x. That simplifies to 2x.
The last thing to do is replace the x with
and that's how we end up with
as the final answer.
----------
In short: we subtract the numbers out front, and then tack on a root 2 at the end.
As another example,
![19√(2)-11√(2) = (19-11)√(2) = 8√(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5dikkmrdmlq6fv26siqd0rnnhptbcm17oq.png)
This is basically the same as saying 19x-11x = (19-11)x = 8x where
![x = √(2)](https://img.qammunity.org/2022/formulas/mathematics/college/mwqyxmanu0ayzx7g9z60byxybdrv16k82i.png)